A scientometric assessment of research publications from ICAR-Central Agroforestry Research Institute - Ramanan S., Suresh; Arunachalam, A.; Rajawat, Brijpal Singh (Indian Journal of Agroforestry, 2021)
Agroforestry research in India is spearheaded by the Indian Council of Agricultural Research (ICAR). Under the aegis of ICAR, Central Agroforestry Research Institute (ICAR-CAFRI) is one of its kind research institute in the entire Asia-Pacific Region for research in agroforestry. Decadal analysis of scientific literature output from the Institute was assessed using bibliometric approach by retrieving research publications from the Scopus database for the period 2000-2021. The data on various research metrics such as number of publications, citations and its relevance, frequently published journals and collaboration level were considered for this analysis. The assessment revealed that a total of 188 papers were published by ICAR-CAFRI during the study period in top journals like Indian Journal of Agricultural Sciences, Range Management and Agroforestry, Agroforestry Systems and Current Science. The dataset also revealed increasing number of the publications in the last decade (2011-2020) compared to 2000-2010 due to growing emphasis on agroforestry globally and nationally. Additionally, performance reflections within institutions are considering the concept of ‘publish’ or ‘perish’ adding to increased publications. It is believed, this research results shall help to reconcile target setting for further performance-oriented research in agroforestry.